The Assembly of Bacteria Living in Natural Environments Shapes Neuronal Integrity and Behavioral Outputs in Caenorhabditis elegans - Sebastian Urquiza-Zurich; Victor Antonio Garcia-Angulo; Paula Burdisso; M. Fernanda Palominos; Lucia Fernandez-Hubeid; Paloma A. Harcha; Juan P. Castillo; Andrea Calixto (mBio, 2023)
ABSTRACT Bacterivore nematodes are the most abundant animals in the biosphere, largely contributing to global biogeochemistry. Thus, the effects of environmental microbes on the nematodes’ life-history traits are likely to contribute to the general health of the biosphere. Caenorhabditis elegans is an excellent model to study the behavioral and physiological outputs of microbial diets. However, the effects of complex natural bacterial assemblies have only recently been reported, as most studies have been carried out with monoxenic cultures of laboratory-reared bacteria. Here, we quantified the physiological, phenotypic, and behavioral traits of C. elegans feeding on two bacteria that were coisolated with wild nematodes from a soil sample. These bacteria were identified as a putative novel species of Stenotrophomonas named Stenotrophomonas sp. strain Iso1 and a strain of Bacillus pumilus designated Iso2. The distinctive behaviors and developmental patterns observed in animals fed with individual isolates changed when bacteria were mixed. We studied in more depth the degeneration rate of the touch circuit of C. elegans and show that B. pumilus alone is protective, while the mix with Stenotrophomonas sp. is degenerative. The analysis of the metabolite contents of each isolate and their combination identified NAD+ as being potentially neuroprotective. In vivo supplementation shows that NAD+ restores neuroprotection to the mixes and also to individual nonprotective bacteria. Our results highlight the distinctive physiological effects of bacteria resembling native diets in a multicomponent scenario rather than using single isolates on nematodes. IMPORTANCE Do behavioral choices depend on animals’ microbiota? To answer this question, we studied how different bacterial assemblies impact the life-history traits of the bacterivore nematode C. elegans using isolated bacteria found in association with wild nematodes in Chilean soil. We identified the first isolate, Iso1, as a novel species of Stenotrophomonas and isolate Iso2 as Bacillus pumilus. We find that worm traits such as food choice, pharyngeal pumping, and neuroprotection, among others, are dependent on the biota composition. For example, the neurodegeneration of the touch circuit needed to sense and escape from predators in the wild decreases when nematodes are fed on B. pumilus, while its coculture with Stenotrophomonas sp. eliminates neuroprotection. Using metabolomics analysis, we identify metabolites such as NAD+, present in B. pumilus yet lost in the mix, as being neuroprotective and validated their protective effects using in vivo experiments.